Graphene Oxide/α‐Bi2O3 Composites for Visible‐Light Photocatalysis, Chemical Catalysis, and Solar Energy Conversion. Issue 3 (27th February 2014) - Som, Tirtha; Troppenz, Gerald V.; Wendt, R. Robert; Wollgarten, Markus; Rappich, Jörg; Emmerling, Franziska; Rademann, Klaus
Abstract The growing challenges of environmental purification by solar photocatalysis, precious‐metal‐free catalysis, and photocurrent generation in photovoltaic cells receive the utmost global attention. Here we demonstrate a one‐pot, green chemical synthesis of a new stable heterostructured, ecofriendly, multifunctional microcomposite that consists of α‐Bi2O3 microneedles intercalated with anchored graphene oxide (GO) microsheets (1.0 wt %) for the above‐mentioned applications on a large economical scale. The bare α‐Bi2O3 microneedles display two times better photocatalytic activities than commercial TiO2 (Degussa‐P25), whereas the GO‐hybridized composite exhibits approximately four to six times enhanced photocatalytic activities than the neat TiO2 photocatalyst in the degradation of colored aromatic organic dyes (crystal violet and rhodamine 6G) under visible‐light irradiation (300 W tungsten lamp). The highly efficient activity is associated with the strong surface adsorption ability of GO for aromatic dye molecules, the high carrier acceptability, and the efficient electron–hole pair separation in Bi2O3 by individual adjoining GO sheets. The introduction of Ag nanoparticles (2.0 wt %) further enhances the photocatalytic performance of the composite over eightfold because of a plasmon‐induced electron‐transfer process from Ag nanoparticles through the GO sheets into the conduction band of Bi2O3. The new composites are also catalytically active and catalyze the reduction of 4‐nitrophenol to 4‐aminophenol in the presence of borohydride ions. Photoanodes assembled from GO/α‐Bi2O3 and Ag/GO/α‐Bi2O3 composites display an improved photocurrent response (power conversion efficiency ∼20 % higher) over those prepared without GO in dye‐sensitized solar cells.